An Analysis of Organizational Citizenship Behavior and its Impact on Employee Well-being and Task Performance among Library Employees - Das, Barttanu Kumar; Rajini, G. (Indian Journal of Information Sources and Services, 2024)
Employees at the library have opinions about things like equality, processes, and how people should act around each other at work. Library workers are more likely to show organizational dedication, do their jobs, take on extra tasks, and be happy with their jobs when they think the workplace is fair. According to an Organizational Citizenship Behavior (OCB) study, library workers who feel unfairly treated are likelier to do bad things like not doing their jobs or trying to get something they do not deserve. To find out what makes library management work, a poll is given to librarians and the library management system to see how well organizational backing, Employee Well-Being (EWB), work liberty, Task Performance (TP), job expectations, and job stress are met. The results show that library management can be improved by giving workers more useful comments on their work and improving how they feel about the organization's help and their level of freedom. Executives make their workplaces more fair using methods focusing on library support, autonomy, and assessment. These methods aim to minimize views of inequality among workers.